2019
DOI: 10.18280/acsm.430606
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Mechanical Parameters of Bacterial Concrete

Abstract: Conventional concrete is prone to cracking under tensile load, despite its good compressive strength. Recently, biological agents have been applied to heal the cracks in concrete, making concrete structures more serviceable. This paper mainly attempts to evaluate the mechanical properties of bacteria-based self-healing concrete. Two bacteria were selected as the bioagents in concrete, namely, Bacillus subtilis and Bacillus halodurans. The concentration of the bioagents were set to 10 5~1 0 7 cell/mL in water. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Bacterial mixtures with chitosan incorporation at 0, 0.5, 1.0 and 1.5% increased strength by 1.97%, 3.44%, 13.79% and 1.48% with respect to the control mixture (Dolomite-sandcement-water-superplasticizer) [47]. In another study, it was found that at 28 days the concrete with B. halodurans with solutions of 10 5 CFU/mL reached the highest strength, being superior to the mixture with B. subtilis at the same concentration [53]. In addition, by using a genetically improved strain (B. subtilis T), a significant increase in resistance was achieved [30].…”
Section: Flexural Strengthmentioning
confidence: 91%
See 1 more Smart Citation
“…Bacterial mixtures with chitosan incorporation at 0, 0.5, 1.0 and 1.5% increased strength by 1.97%, 3.44%, 13.79% and 1.48% with respect to the control mixture (Dolomite-sandcement-water-superplasticizer) [47]. In another study, it was found that at 28 days the concrete with B. halodurans with solutions of 10 5 CFU/mL reached the highest strength, being superior to the mixture with B. subtilis at the same concentration [53]. In addition, by using a genetically improved strain (B. subtilis T), a significant increase in resistance was achieved [30].…”
Section: Flexural Strengthmentioning
confidence: 91%
“…An important aspect of this type of studies is to evaluate the mechanical properties of selfrepairing concrete considering the type of bacteria and the concentration of bioagents, thus, it has been identified that at 28 days of curing, mixtures with B. halodurans and B. subtilis are superior to conventional concrete (7% and 18% higher, respectively) [53]. Likewise, several studies report the use of other types of bacteria that improve compressive strength over conventional strength, among them we have: B. sphaericus (15.95%), B. cohnii (11.45%), and B. megaterium MTCC 1684 (16%) [54]; B. megaterium MTCC 1684 (14.8%), and Lysinibacillus sp.…”
Section: Compressive Strengthmentioning
confidence: 99%
“…The compressive strength of cement is satisfactory, but its tensile strength is different [42]. As we have expressed in the previous discussion, a method of healing cracks via bacteria offers a change in concrete structures.…”
Section: Effect Of Bacteria On Increasing the Mechanical Properties O...mentioning
confidence: 93%
“…All the prepared concrete samples are cured in normal water for 28 days before testing. The surface cracks are formed using 65% and 75% stress level concentrations [16]. To evaluate the healing ability of bacterial agents, three different curing conditions are adopted, namely water, calcium lactate, and air (i.e., ambient curing).…”
Section: Experimental Methodologymentioning
confidence: 99%
“…Self-healing concrete is the one that heals itself when it comes into air, water and produces lime on the outer layer of the concrete. The self-healing process can be broadly classified into two types, i.e., autogenous self-healing and autonomous self-healing and the healing methods are shown in Fig 1 . The healing can be done with many materials like biological agents [14][15][16][17][18][19], chemical agents, superabsorbent polymers, crystalline materials, pozzolanic materials [20][21][22] and mineral admixtures that are added and replaced with cement in order to arrest the cracks of concrete which shortens their production.…”
Section: Introductionmentioning
confidence: 99%